Research on the Development and Teaching of Thinking Skills - Margarita Amestoy de Sánchez (Universidad Autónoma de Baja California, 2002)
In this presentation it is proposed and justified an integrated model of research and development that could be applicable to the building, implementation and evaluation of the teaching and transfer of thinking skills. First, the principles underlying the development of thought are presented; next, the role of research in the construction and application of the intellectual development and process-based learning model; its components and interrelations are identified. Finally, the role of research in the design and application of projects aiming at the development of thinking skills is analyzed.